POPULATION DATA PROGRAM APPLICATION IN SCOPE Neighborhood / RT USING Visual FoxPro 9.0 - Ari Purwaningsih; Hariyanto Hariyanto Skom, MMsi (Jurnal Sistem Informasi, 2008)
Scientific writing is about a population in the Scope of Application ProgramNeighborhood / RT. Because in this sphere should be applied computerization shouldhave started well in terms of managing the administration of residents such ascreating a Letter of Introduction to ID cards, Family Card, Letter Swap, or other datarelated to population problems in the future so that there is no longer the process ofrecording. Repeated data as well as a waste of time and cost is not small.Residential Program Application is using Microsoft Visual FoxPro 9.0 for usingMicrosoft Visual FoxPro 9.0 Population data management application is designed tobe easy by utilizing the various facilities provided by Microsoft Visual FoxPro 9.0, soit is easy to use application.